Alternative suppression of Botrytis cinerea in strawberry using essential oils - Santos, Camila Ferreira dos; Pohlmann, Valeria; Ludwig, Fernanda (Scientia Agraria Paranaensis, 2021)
Strawberry (Fragaria x ananassa) is a perishable fruit with a short post-harvest life and a high incidence of fungal diseases, especially Botrytis cinerea. For control and prevention, synthetic products are often used which negatively influence in the food and environmental security. The present work was carried out with the objective of evaluating the inhibitory potential of essential oils in the growth and control of the B. cinerea in vitro and in vivo. The essential oils of thyme (Thymus vulgares L.), cinnamon (Cinnamomum cassia L.), lemongrass (Cymbopogon flexuosus L.), peppermint (Mentha piperita L.) and tea tree (Melaleuca alternifolia Maiden & Betche) were tested, in addition to control made of autoclaved water, using a completely randomized design with 4 replications. The fungus growth was evaluated in vitro through grading. Strawberry fruits were evaluated for the presence of B. cinerea, firmness and total soluble solids content. The growth of the B. cinerea in vitro, the percentage of gray mold infection, the total soluble solids content and the texture of strawberry were evaluated. The in vitro growth of the fungus received lower scores with the essential oils of thyme and cinnamon, with values of 0.32 and 0.92, respectively, with greater suppression. The percentage of strawberry with symptoms were lower than the treatments with tea tree (8,33%), thyme (25%), lemongrass (25%) and peppermint (26,66%). The essential oils of thyme and cinnamon have potential for use in the control of the Botrytis cinerea in in vitro test and the essential oils of peppermint, thyme, tea tree and lemongrass have potential for use in the suppression in strawberry fruits.